Analysis of Macroeconomic Determinants and Banking Performance on Non-Performing Loans of Regional Development Banks in Indonesia - Fadli Adinda Harahap (ProBisnis : Jurnal Manajemen, 2022)
The objectives of this research is to analyze the effect of macroeconomic and bank performance determinants toward Non Performing Loans (NPL) of Regional Development Banks (BPD) in Indonesia during the period 2020-2021. The objects of this research are 26 Regional Development Banks. Macroeconomic variables that are used are regional economic growth and inflation. Then bank performance variables that used are Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and loan growth This research uses panel data regression analysis method and goodness of fit test (t test, F test, and R-squared test ). Based on the result of model selection test by using Hausman test, Random Effect Model is the appropriate model for this research. The estimation result shows that simultaneously regional economic growth, inflation, LDR, CAR, and loan growth have significant effect to NPL. Partially, only loan growth has significant effect to NPL with negative association. Meanwhile, regional economic growth, inflation, LDR, and CAR have no significant effect to the NPL of Regional Development Bank (BPD) during the period 2020-2021.